2020
DOI: 10.3389/fonc.2020.594590
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea in Patients Receiving Radical Radiotherapy for Non-Small Cell Lung Cancer: A Prospective Study

Abstract: Background and PurposeDyspnea is an important symptomatic endpoint for assessment of radiation-induced lung injury (RILI) following radical radiotherapy in locally advanced disease, which remains the mainstay of treatment at the time of significant advances in therapy including combination treatments with immunotherapy and chemotherapy and the use of local ablative radiotherapy techniques. We investigated the relationship between dose-volume parameters and subjective changes in dyspnea as a measure of RILI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As this study focused on lung cancer patients with IP, PT can be considered to be a less invasive treatment. However, the changes in QLQ-LC13 dyspnea scores seen at 3 months after radiotherapy have been shown to be correlated with lung V 30Gy , V 40Gy , V 50Gy , and MLD values [ 52 ]. Previous studies have suggested that a lung V 40Gy cut-off value of 11% exhibits good sensitivity and specificity as a predictor of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…As this study focused on lung cancer patients with IP, PT can be considered to be a less invasive treatment. However, the changes in QLQ-LC13 dyspnea scores seen at 3 months after radiotherapy have been shown to be correlated with lung V 30Gy , V 40Gy , V 50Gy , and MLD values [ 52 ]. Previous studies have suggested that a lung V 40Gy cut-off value of 11% exhibits good sensitivity and specificity as a predictor of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, in order to account for different fractionation regimens, the BED-VH metrics were extracted and the V 15Gy|α/β=3 resulted to be an independent dose metric predictor for dyspnea, an important symptomatic endpoint for assessment of RILD [45]. Notably, the use of the adopted BED model is not universally accepted, especially when large fraction sizes are considered.…”
Section: Resultsmentioning
confidence: 99%
“…As this study focused on lung cancer patients with IP, PT can be considered to be a less invasive treatment. However, the changes in QLQ-LC13 dyspnea scores seen at 3 months after radiotherapy have been shown to be correlated with lung V 30Gy , V 40Gy , V 50Gy , and MLD values [43].…”
Section: Discussionmentioning
confidence: 97%